Lamivudine 24-month-long prophylaxis is a safe and efficient choice for the prevention of hepatitis B virus reactivation in HBsAg-negative/HBcAb-positive patients with advanced DLBCL undergoing upfront R-CHOP-21 - Giordano, Claudia; Picardi, Marco; Pugliese, Novella; Vincenzi, Annamaria; Abagnale, Davide Pio; De Fazio, Laura; Giannattasio, Maria Luisa; Fatigati, Carmina; Ciriello, Mauro; Salemme, Alessia; Muccioli Casadei, Giada; Vigliar, Elena; et al. (Frontiers in Oncology, 2023)
Occult hepatitis B infection (OBI) is a condition where replication-competent Hepatitis B virus-DNA (HBV-DNA) is present in the liver, with/out HBV-DNA in the blood (<200 international units [IU]/ml or absent) in HB surface antigen (HBsAg) negative/HB core antibody (HBcAb) positive individuals. In patients with advanced-stage diffuse large B cell lymphoma (DLBCL) undergoing 6 cycles of R-CHOP-21+2 additional R, OBI reactivation is a frequent and severe complication. There is no consensus among recent guidelines whether a pre-emptive approach or primary antiviral prophylaxis is the best solution in this setting of patients. In addition, questions still unresolved are the type of prophylactic drug against HBV and adequate prophylaxis duration. In this case-cohort study, we compared a prospective series (from January 2018 to December 2020) of 31 HBsAg-/HBcAb+ patients with newly diagnosed high-risk DLBCL receiving 100 mg daily lamivudine (LAM) prophylaxis 1 week before R-CHOP-21+2R until 18 months after (24-month LAM series), versus 96 HBsAg-/HBcAb+ patients (from January 2005 to December 2011) undergoing a pre-emptive approach (pre-emptive cohort) and versus 60 HBsAg-/HBcAb+ patients from January 2012 to December 2017 receiving LAM (same schedule except for the suspension at 6 months after the completion of immunochemotherapy [ICHT]) prophylaxis (12-month LAM cohort). Efficacy analysis focused primarily on ICHT disruption and secondarily on OBI reactivation and/or acute hepatitis. In the 24-month LAM series and in the 12-month LAM cohort there were no episodes of ICHT disruption vs 7% in the pre-emptive cohort (P= 0.05). OBI reactivation didn’t occur in any of the 31 patients in the 24-month LAM series versus 7/60 patients (10%) in the 12-month LAM cohort or 12/96 (12%) patients in the pre-emptive cohort (P = 0.04, by χ2 test). No patients in the 24-month LAM series developed acute hepatitis compared with 3 in the 12-month LAM and 6 in the pre-emptive cohort. This is the first study collecting data regarding a consistent and homogenous large sample of 187 HBsAg-/HBcAb+ patients undergoing standard R-CHOP-21 for aggressive lymphoma. In our study, 24-month long prophylaxis with LAM appears to be the most effective approach with a null risk of OBI reactivation, hepatitis flare-up and ICHT disruption.